Densification, flexural strength and dielectric properties of CaO-MgO-ZnO-SiO2/Al2O3 glass ceramics for LTCC applications. Issue 20 (15th October 2021) - Xiang, Liutong; Zhong, Chaowei; Qin, Tianyin; Wang, Mingxia; Liu, Dongshuo; Tang, Bin; Shuren zhang,
Abstract: Novel glass ceramics for LTCC applications with high flexural strength can be achieved by CaO-MgO-ZnO-SiO2 (CMSZ) glass cofiring with Al2 O3 . The sintering shrinkage behavior, crystalline phases, mechanical and dielectric properties, and thermal expansion of the CMZS/Al2 O3 glass ceramic were determined. The X-ray diffraction results revealed that multiphases (CaMgSi2 O6, Al2 Ca(SiO4 )2 and ZnAl2 O4 ) formed in the sintering process of the CMZS/Al2 O3 glass ceramic. The flexural strength of CMZS/Al2 O3 glass ceramics first increases and then decreases with increasing Al2 O3 content. The CMZS/Al2 O3 glass ceramic with 50 wt % Al2 O3 sintered at 890 °C for 2 h achieved the best performance, with a maximum flexural strength of 256 MPa, dielectric constant (εr ) of 7.89, dielectric loss (tan δ) of 3.41 × 10 −3 (12 GHz), temperature coefficient of resonance frequency (τ f ) of −29 ppm/°C, and the CTE value of 7.93 × 10 −6 /°C.